If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(k + 2) + -1 + 4k = 0 Reorder the terms: -3(2 + k) + -1 + 4k = 0 (2 * -3 + k * -3) + -1 + 4k = 0 (-6 + -3k) + -1 + 4k = 0 Reorder the terms: -6 + -1 + -3k + 4k = 0 Combine like terms: -6 + -1 = -7 -7 + -3k + 4k = 0 Combine like terms: -3k + 4k = 1k -7 + 1k = 0 Solving -7 + 1k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1k = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1k = 0 + 7 1k = 0 + 7 Combine like terms: 0 + 7 = 7 1k = 7 Divide each side by '1'. k = 7 Simplifying k = 7
| 12=a-3.8 | | x^3+5x^2+100s=0 | | 3x(2x-3)=105 | | 2(y-7)+10=12 | | X+3003+y=7867 | | 5-(8-d)-52=19d-6(2+4d) | | 1v+11-15v=5 | | 6y-3fromy-10= | | 6y+2(y-8)=6(y+1)-3 | | .25=x+(2-x) | | 0.54+0.33t=2.40t-0.84 | | 6-2f+3f=6f-9 | | 3p+2q=-21 | | Y+14=14 | | 2.6x+58.3=35.7-8.7x | | 5+8z=-7z-10 | | 5y-y-9y= | | 6x+18=13x-55 | | 3x+(-2)=16 | | 2sinx-2cosx=1 | | -6v+7=7-5v | | -(3x-11)+2(5x+7)= | | 3x-25=27+x | | cos(2x)+9cos(x)+5=0 | | 10x-5=-45 | | 24f=144-8f^2 | | 3x+7+8x-15=5x+7x | | 350+15a=299+18a | | 16-4w-4w-w^2= | | 6+2x=-20 | | -8y+6=2x | | -48j=-9j^2-39 |